2009
DOI: 10.1007/s10096-009-0711-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of meropenem alone and combined with rifampin in the guinea pig model of pneumococcal meningitis

Abstract: Meropenem is a broad-spectrum carbapenem antibiotic that is highly active against the pathogens causing meningitis. The aims of this study was to determine the efficacies of meropenem alone and combined with rifampin against two Streptococcus pneumoniae strains with different susceptibility to beta-lactams using the guinea pig meningitis model and compare them with the standard ceftriaxone plus vancomycin therapy. All treatments except rifampin were bactericidal from 6 h. The addition of rifampin did not impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, 2 separate in vivo studies of experimental PRSP meningitis comparing ceftriaxone to combination therapy with rifampin found that rifampin combination therapy was highly effective (211,236). The addition of rifampin to meropenem did not improve the clearance of PRSP in a guinea pig model (88).…”
Section: Other Diseasesmentioning
confidence: 98%
“…However, 2 separate in vivo studies of experimental PRSP meningitis comparing ceftriaxone to combination therapy with rifampin found that rifampin combination therapy was highly effective (211,236). The addition of rifampin to meropenem did not improve the clearance of PRSP in a guinea pig model (88).…”
Section: Other Diseasesmentioning
confidence: 98%